Analysis of the Potential Nature Tourism of Perintis Lake in the Huluduotamo Village of Suwawa District, Bone Bolango Regency - Irwan Wunarlan; Nilawaty Yusuf (Journal of International Conference Proceedings (JICP), 2018)
Perintis Lake has an area of ± 11.09 Ha is one of the natural tourism in the Bone Bolango Regency has the potential to attract tourists and travelers both domestic and non-domestic. The Perintis Lake position has become important for the tourism sector, but its contribution has not been significant in the GDP structure of Bone Bolango Regency. This is due to the lack of public facilities, rides and tourist attractions as well as various souvenirs at around Perintis Lake so that serious attention from stakeholders is needed if they wants to make Perintis Lake a tourist destination so as to provide an effect multiplier for tourism entrepreneurs and regional economic. This study will examine the potential and supporting facilities of Perintis Lake natural tourism and their development strategies. The research method used is descriptive quantitative with the research locus on the natural tourism of Perintis Lake in Huluduotamo Village. The research was conducted from April to August 2018. Data collection techniques and sampling were questionnaires and accidental sampling, the number of samples was 62 respondents. The answers to the questionnaire are set using the Likert scale with closed question types. The results of the questionnaire were analyzed with intervals score and SWOT. Generally, natural tourism of Perintis Lake are potential enough to be developed into tourist destinations. The strategy that must be carried out by tourism stakeholders is the SO strategy (Strategic-Opportunity) or an aggressive strategy so that tourism services and foreign exchange outcomes are also optimal. Keywords: nature tourism, lake, potential, tourists